The Influence of Career Development, Work-Life Balance, and Compensation on Employee Job Satisfaction - Rifaldi Rifaldi; Zam Zam Zainal Mutaqin; Ade Solahudin; Sunimah Sunimah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research seeks to examine how career progression, work-life harmony, and remuneration affect job satisfaction among employees at PT Wijaya Gyokai Indonesia. In the context of increasingly fierce business competition, effective human resource management is the key to the company's success. The chosen research design is quantitative with primary data collection through observation, interviews, and questionnaires, involving 150 employees as samples. Findings from the analysis indicate that both career advancement and financial rewards exert a positive and statistically significant impact on employee satisfaction. In contrast, work-life balance appears to have no meaningful effect. Simultaneously, the three factors contribute 41.1% to the variation in job satisfaction. The findings emphasize the importance of companies in improving career development programs and fair compensation systems to increase employee job satisfaction, while the work-life balance aspect needs a more contextual approach to have a more significant impact.